Fluid iron : state formation in Southeast Asia - Day, Tony (Honolulu : University of Hawaii Press, 2002)
Fluid Iron is the first extended treatment of state formation in Southeast Asia from early to contemporary times and the first book-length analysis of Western historical and ethnographic writing on the region. It includes critical assessments of the work of Clifford Geertz, O.W. Wolters, Benedict Anderson, and other major scholars who have written on early, colonial, and modern Southeast Asian history and culture. Making use of the ideas of Weber, Marx, Foucault, and postmodern and postcolonial theory, Tony Day argues that culture must be restored to the study of Southeast Asian history so that the state and historical developments in the region can be returned to their own "alternative" historical contexts and trajectories. He employs a wide range of contemporary scholarship, as well as Southeast Asian literary and historical texts, inscriptions, and temples to explore the kinds of concepts and practices--kinship networks, cosmologies, gender identities, bureaucracies, rituals, violence and aesthetics--that have been used for centuries to build states
Machine generated contents note: 1. Studying the State in Southeast Asia: Definitions, Problems, Approaches -- 2. Ties That (Un)Bind -- 3. Cosmologies, Truth Regimes, and Invulnerability -- 4. Bureaucracy, Reason, and Ritual -- 5. Violence and Beauty -- Conclusion: Alternative States, Incongruous Region.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
In English.
digitized
JSTOR
Keywords: Southeast Asia -- Politics and government; State, The; État.; Asie du Sud-Est -- Politique et gouvernement; HISTORY; HISTORY -- Asia -- Southeast Asia; Politics and government; State, The; Southeast Asia; Staatsvorming; 15.75 history of Asia; Politik; Staat; Südostasien; Geschiedenis (vorm)